PENERAPAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MENGGUNAKAN PERALATAN DAN PERLENGKAPAN DITEMPAT KERJA SISWA KELAS X DI SMK TAMANSISWA NANGGULAN KULON PROGO TAHUN AJARAN 2015/2016 - Deni Cahyono; setuju setuju (Universitas Sarjanawiyata Tamansiswa, 2017)
Deni cahyono. 2012006090. The application of Learning Models Numbered Head Together (NHT) for the activities and the results of learning to use tools and equipment with respect to improve the work of Students of class X in SMK Tamansiswa Nanggulan Kulon Progo academic year 2015/2016. Thesis Course Education of Mechanical Engineering Faculty of teacher training and Educational Sciences University Sarjanawiyata Tamansiswa Yogyakarta 2016. The purpose of the research to know the activities and results of the study grade SMK X Tamansiswa Nanggulan academic year 2015/2016 using the learning model Numbered Head Together (NHT). The research is the research action class that consists of three cycles. The subject of research that is grade I TKR with the amount X 26 students and the object of research activities and results, namely learning to use tools and equipment at the places of work with the learning model Numbered Head Together (NHT). Data collection using the observation sheet activity of students and test results of student learning. Improvement of the learning outcomes each cycle using a pretestand posttest. The validity ofthe instrument using expert judgement. Data analysis techniques using qualitative and quantitative data.The results showed the average student activity increased from cycle I to cycle II of 16,66%, from cycle II to cycle III of 23.73% and the whole learning outcomes students in class on the pretest of 52.31 experienced an increase in cycle I of 67.50 or increased by 29.03%.Next cycle I to cycle II an increase in student learning outcomes i.e. from 67.50 rises to 72.26 or increased by 7,05%. Then from cycle II to cycle III results average learning students also increased, rising to 72.26 from 90.96 or increased by 11.56%. So with increasing student learning activities have an impact on the improvement of student learning outcomes.